Sitravatinib, a Tyrosine Kinase Inhibitor, Inhibits the Transport Function of ABCG2 and Restores Sensitivity to Chemotherapy-Resistant Cancer Cells in vitro - Yang, Yuqi; Ji, Ning; Teng, Qiu-Xu; Cai, Chao-Yun; Wang, Jing-Quan; Wu, Zhuo-Xun; Lei, Zi-Ning; Lusvarghi, Sabrina; Ambudkar, Suresh V.; Chen, Zhe-Sheng (Frontiers in Oncology, 2020)
Sitravatinib, also called MGCD516 or MG-516, is a broad-spectrum tyrosine kinase inhibitor (TKI) under phase III clinical evaluation. Herein, we explored the activity of sitravatinib toward multidrug resistance (MDR) by emphasizing its inhibitory effect on ATP-binding cassette super-family G member 2 (ABCG2). ABCG2 is a member of ATP-binding cassette (ABC) transporter family and plays a critical role in mediating MDR. Sitravatinb received an outstanding docking score for binding to the human ABCG2 model (PDB code: 6ETI) among thirty screened TKIs. Also, an MTT assay indicated that sitravatinib at 3 μM had the ability to restore the antineoplastic effect of various ABCG2 substrates in both drug-selected and gene-transfected ABCG2-overexpressing cell lines. In further tritium-labeled mitoxantrone transportation study, sitravatinib at 3 μM blocked the efflux function mediated by ABCG2 and as a result, increased the intracellular concentration of anticancer drugs. Interestingly, sitravatinib at 3 μM altered neither protein expression nor subcellular localization of ABCG2. An ATPase assay demonstrated that ATPase activity of ABCG2 was inhibited in a concentration-dependent manner with sitravatinib; thus, the energy source to pump out compounds was interfered. Collectively, the results of this study open new avenues for sitravatinib working as an ABCG2 inhibitor which restores the antineoplastic activity of anticancer drugs known to be ABCG2 substrates.